GPCR crystal structures: Medicinal chemistry in the pocket. Issue 14 (15th July 2015) - Shonberg, Jeremy; Kling, Ralf C.; Gmeiner, Peter; Löber, Stefan
Graphical abstract: Abstract: Recent breakthroughs in GPCR structural biology have significantly increased our understanding of drug action at these therapeutically relevant receptors, and this will undoubtedly lead to the design of better therapeutics. In recent years, crystal structures of GPCRs from classes A, B, C and F have been solved, unveiling a precise snapshot of ligand–receptor interactions. Furthermore, some receptors have been crystallized in different functional states in complex with antagonists, partial agonists, full agonists, biased agonists and allosteric modulators, providing further insight into the mechanisms of ligand-induced GPCR activation. It is now obvious that there is enormous diversity in the size, shape and position of the ligand binding pockets in GPCRs. In this review, we summarise the current state of solved GPCR structures, with a particular focus on ligand–receptor interactions in the binding pocket, and how this can contribute to the design of GPCR ligands with better affinity, subtype selectivity or efficacy.